The Inland Revenue Authority of Singapore : recent service innovations and their effects on taxpayers - Lim, Roderick Yong Guan (2014)
Intense market competition and the increasing expectations of the public have encouraged many government bodies to become statutory boards, or even private corporations. This conversion enabled them to adopt corporate philosophies and become more service-oriented in their operations.